2012
DOI: 10.1007/s10461-012-0236-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Socioeconomic Inequality in the Incidence of AIDS: Rural–Urban Considerations

Abstract: Low socioeconomic status (SES) influences the risk of acquiring human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) and thus should be considered when analyzing HIV/AIDS surveillance data. Most surveillance systems do not collect individual level SES data but do collect residential ZIP code. We developed SES deprivation indices at the ZIP code tabulation area and assessed their predictive validity for AIDS incidence relative to individual neighborhood-level indicators in Florida using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…Thirteen neighborhood-level SES indicators were extracted from the ACS (Niyonsenga et al, 2013): percent of households without access to a car, percent of households with ≥1 person per room, percent of population living below the poverty line, percent of owner-occupied homes worth ≥$300,000, median household income in 2011, percent of households with annual income <$15,000, percent of households with annual income ≥$150,000, income disparity (derived from percent of households with annual income <$10,000 and percent of households with annual income ≥$50,000), percent of population age ≥25 with less than a 12 th grade education, percent of population age ≥25 with a graduate professional degree, percent of households living in rented housing, percent of population age ≥16 who were unemployed, and percent of population age ≥16 employed in high working class occupation. We additionally extracted percent of population who identified as Hispanic or Latino from the ACS.…”
Section: Methodsmentioning
confidence: 99%
“…Thirteen neighborhood-level SES indicators were extracted from the ACS (Niyonsenga et al, 2013): percent of households without access to a car, percent of households with ≥1 person per room, percent of population living below the poverty line, percent of owner-occupied homes worth ≥$300,000, median household income in 2011, percent of households with annual income <$15,000, percent of households with annual income ≥$150,000, income disparity (derived from percent of households with annual income <$10,000 and percent of households with annual income ≥$50,000), percent of population age ≥25 with less than a 12 th grade education, percent of population age ≥25 with a graduate professional degree, percent of households living in rented housing, percent of population age ≥16 who were unemployed, and percent of population age ≥16 employed in high working class occupation. We additionally extracted percent of population who identified as Hispanic or Latino from the ACS.…”
Section: Methodsmentioning
confidence: 99%
“…29 Another study conducted in the southern US found that the influence of socioeconomic deprivation on HIV/AIDS incidence was impacted by whether one lived in a rural or urban zip code. 30 There remains a gap in the scientific literature regarding whether city of residence is a marker of factors-like poverty-that affect HIV risk and experiences of economic, legal, and social hardships among Black MSM.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neighborhood poverty has been shown to partially account for racial/ethnic disparities in HIV/AIDS survival (Trepka et al, 2013, Arnold et al, 2009) and antiretroviral initiation (Arnold et al, 2009). Possible mechanisms to the relationship between neighborhood-level SES and health include increased psychological stress, decreased positive social networks, and fewer health and social support services (Boardman et al, 2001, Galea et al, 2003, Kirby & Toshiko, 2005.…”
Section: Haartmentioning
confidence: 99%
“…Income disparity was calculated as the logarithmic of 100 times the percent of households with annual income <$10,000 divided by the percent of households with annual income ≥$50,000 and was used as a proxy measure of the Gini-coefficient (Niyonsenga et al, 2013;Singh and Siahpush, 2002). All neighborhood-level indicators were coded so that higher scoresmeant higher poverty and were standardized (Niyonsenga et al, 2013). The percent of Latinos/Hispanics in a neighborhood was divided into 3 categories: <25%, 25-49%, and ≥50% Levy 2012, Shaw et al, 2010).…”
Section: Individual-and Neighborhood-level Variablesmentioning
confidence: 99%
See 1 more Smart Citation